Performance of anaerobic sequencing batch reactors (pilot-scale) in domestic sewage treatment - Eugenio Foresti; Marcelo Zaiat; Arnaldo Sarti (Semina: Ciências Exatas e Tecnológicas, 2005)
This study shows the results obtained during 70 days using four pilot scale anaerobic sequencing batch reactors, for sewage system treatment of the campus of the University of São Paulo in São Carlos – SP. Each reactor system with 1.2 m³ of total volume, was designed for the treatment of 1.95 m³d³ of domestic sewage, with geometrical conceptions (ratio H-height/D-diameter), mechanical conceptions (mechanical mixing or liquid re-circulation) and different biomass retention type. Three of them were ASBR (AnaerobicSequencing Batch Reactor) with granular biomass and another one was an ASBBR (Anaerobic Sequencing Batch Biofilm Reactor) with biomass consisting of cubic matrices of polyurethane foam. The reactors were inoculated and operated within an 8-hour batch cycle. The reactors monitoring included the oxygen chemical demand (OCD), pH, total suspended solids (TSS) and volatile suspended solids, volatile fatty acids, alkalinity to bicarbonate and methane concentration. Both ASBR reactors with liquid re-circulation did not show a satisfactory performance. The average values of OCD and TSS removal were close to 40% and 60% respectively. In the ASBR reactors with mechanical mixing and ASBBR with immobilized biomass, showed better results. The ASBBR reactor reached average efficiency of 61% and 75% in OCD and TSS removal, while in the ASBR with mechanical mixing, it reached 60% and 79%, respectively.